Bacteroides fragilis polysaccharide A induces IL-10 secreting B and T cells that prevent viral encephalitis - Chandran Ramakrishna (Nature Portfolio, 2019)
The capsular polysaccharide A (PSA) of Bacteroides fragilis is known to have immunomodulatory capability during sterile inflammatory disorders. Here Ramakrishna and colleagues show that PSA administration in a murine model of herpes simplex encephalitis induces IL-10 producing B and T cell populations that confer protection against lethal challenge and brain pathology.